Uncharacteristic behaviour in low temperature of conductive polypyrrole detected by temperature-dependent terahertz transmission spectroscopy - Quema, Alex (Animo Repository, 2005)
Conductive polypyrroles are characterized using temperature-dependent terahertz (THz) spectroscopy. At 100K, THz radiation power started to level off and an absorption peak is manifested. This is attributed to the disorder generated during synthesis and doping processes, which plays a critical role in the microscopic disorder and/or structural amorphous regions of the polymer. © 2005 IEEE.